Improvement on the design and fabrication of planar SOFCs with anode–supported cells based on modified button cells. (December 2018) - Nguyen, Xuan-Vien; Chang, Chang-Tsair; Jung, Guo-Bin; Chan, Shih-Hung; Yeh, Chia-Chen; Yu, Jyun-Wei; Lee, Chi-Yuan
Abstract: In this study, a planar solid oxide fuel cells (SOFCs) apparatus with a 6 cm × 6 cm anode supported single cell based on a modified button cell was designed for operation in both regular cell and button cell configurations. The apparatus was assembled with a regular cell with an active area of 5 cm × 5 cm and with a button cell with an active area of 2.54 cm 2 . They consist of fuel and oxidant chambers that allow heat conversion and thus increase the temperatures of the fuel inlet and oxidant inlet streams. The chambers reduced the cooling effect, thereby improved the cell performance. In addition, a wire–in–tube–type heat exchanger was designed and fabricated. This device was installed in front of the fuel inlet of the SOFC apparatus to improve heat transfer to better increase the temperature of the fuel inlet stream. Results indicate that the fuel outlet temperature of the system with heat exchanger is much higher than that of the system without heat exchanger. Thus, the performance of system with heat exchanger is largely improved. This improvement means that the wire–in–tube type heat exchanger is proved to be effectively increases the hydrogen inlet temperature by enhancing heat transfer. Highlights: A design of planar SOFC based on a modified button cell was designed and fabricated. A wire–in–tube–type heat exchanger was designed and fabricated. Regular cells, which are equivalent to 5 cm × 5 cm unit cells and button cells with a 2.54 cm 2 active area, were operated successfully. The fuel outlet temperature of the system with the heat exchanger is much higher than that of the system without the heat exchanger.